Ligand‐Induced Dimerization of a Truncated Parallel MYC G‐Quadruplex. (1st February 2018) - Funke, Andrea; Karg, Beatrice; Dickerhoff, Jonathan; Balke, Darko; Müller, Sabine; Weisz, Klaus
Abstract: Binding of an indoloquinoline derivative with an aminoalkyl side chain to a truncated sequence from the MYC promoter region was studied through isothermal titration calorimetry (ITC). The targeted MYC3 sequence lacks 3′‐flanking nucleotides and forms a monomeric parallel quadruplex (G4) with a blunt‐ended 3′‐outer tetrad under the solution conditions employed. Analysis of ITC isotherms reveals multiple binding equilibria with the initial formation of a 1:2 ligand/quadruplex complex. Evaluation of electrophoretic mobilities as well as NMR spectral data confirm ligand‐induced dimerization of MYC3 quadruplexes with the ligand sandwiched between the two 3′‐outer tetrads. Additional ligand molecules in excess bind to the 5′‐outer tetrads of the sandwich complex. Such a ligand‐promoted G4 dimerization may be exploited for the controlled assembly or disassembly of G4 aggregates to expand on present quadruplex‐based technologies. Abstract : An indoloquinoline derivative induces dimerization of a parallel G‐quadruplex that lacks a 3′‐overhang sequence. Formed complexes exhibit a ligand sandwiched between the two blunt‐ended 3′‐tetrads. Formation of the sandwich‐type complex is supported by enhanced stacking energies but is also suggested to rely on additional ligand side‐chain interactions.